Pattern and modes of presentation of varicose veins of lower limbs - NC, Rohit; ML, Manjunath (International Journal of Research in Medical Sciences, 2017)
Background: Varicose veins of the lower extremities are one of the most common peripheral vascular diseases and calls for treatment. Therefore the present study was undertaken to study the pattern and various modes of presentation of the patient with varicosities of the lower limbs. Methods: The study was conducted in teaching & general hospital and government general hospital, attached to medical college. A detail clinical history was taken and a thorough clinical examination was done. The signs and symptoms of patients were reported. Results: 42 cases were afflicted with varicose veins of the lower extremities comprising only 10.99% of the total admissions with vascular complaints. Maximum incidence was in the age group 21-40 years (61.9%). 57.14% of cases were involved in occupation requiring prolonged periods of standing and/ or violent muscular contraction. The most common presenting complaint was pain which varied from dragging pain to night cramps associated with heaviness of the limbs. Edema was present in 11 cases, predominantly localized to below knee with pitting nature. Conclusion: Our study revealed that the disease is most prevalent in the 2nd and 3rd decades of life. We concluded that occupation involving prolonged standing and/or violent muscular contractions contribute to or precipitate varicose veins if not actually cause them.